Digital Business Model Development Strategy in the Era of Digital Transformation: A Case Study on Technology Startups - Ardiansyah; Hastuti, Juria; Yusmanidar; Sarno (Journal Informatic, Education and Management (JIEM), 2025)
Digital transformation has significantly changed the business landscape, encouraging technology startups to adapt innovative and sustainable business model development strategies. This research aims to identify and analyze digital business model development strategies implemented by technology startups in the face of digital transformation dynamics. A qualitative approach is used in this research with a case study method on several technology startups in Indonesia. Data were collected through in-depth interviews with startup founders and managers, as well as document analysis and direct observation. The results show that there are three main strategies in developing digital business models, namely: (1) the application of artificial intelligence-based technology and data analytics to increase the added value of products and services, (2) strengthening the digital ecosystem through strategic collaboration with business partners and stakeholders, and (3) flexible and subscription-based revenue models to improve business sustainability. In addition, adaptation to regulations and market trends is a key factor in the successful implementation of digital business models. The conclusion of this study confirms that the success of startups in developing digital business models depends not only on technological innovation, but also on the ability to adapt to changes in the business environment. This study contributes to academics and practitioners in understanding the dynamics of digital business models as well as strategies that can be applied to improve startup competitiveness in the era of digital transformation.